2004
DOI: 10.1007/s00213-003-1574-z
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal ethanol exposure produces a hyperalgesia that extends into adolescence, and is associated with increased analgesic and rewarding properties of nicotine in rats

Abstract: Persistent decreases in tail-flick response latencies suggestive of hyperalgesia were observed following neonatal ethanol exposure in the rat. These changes were accompanied by increases in the analgesic and place-conditioning effects of nicotine in adolescence. If similar effects occur in humans, prenatal alcohol exposure may play a role in an increased risk for the rewarding effects and dependence liability of nicotine later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 68 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…Using rats some investigators have found that nicotine will condition an increase in time spent in the paired environment ([Ashby et al, 2002], [Calcagnetti and Schechter, 1994], [Dewey et al, 1999], [Forget et al, 2005], [Forget et al, 2006], [Fudala et al, 1985], [Fudala and Iwamoto, 1986], [Horan et al, 1997], [Horan et al, 2001], [Shoaib et al, 1994] and [Shram et al, 2006]). In contrast, other researchers have reported either avoidance (i.e., an aversion) of the nicotine-paired environment ( [Fudala and Iwamoto, 1987], [Horan et al, 1997] and [Jorenby et al, 1990]) or no place conditioning , , [Clarke and Fibiger, 1987], [Rogers et al, 2004], [Shoaib et al, 1994] and [Shram et al, 2006]). Some potential factors that might explain the inconsistent results include age and strain of the rat, pre-exposure to nicotine, and use of a biased versus unbiased procedure (see LeFoll and Goldberg (2005) for a more detailed review).…”
Section: Introductionmentioning
confidence: 90%
“…Using rats some investigators have found that nicotine will condition an increase in time spent in the paired environment ([Ashby et al, 2002], [Calcagnetti and Schechter, 1994], [Dewey et al, 1999], [Forget et al, 2005], [Forget et al, 2006], [Fudala et al, 1985], [Fudala and Iwamoto, 1986], [Horan et al, 1997], [Horan et al, 2001], [Shoaib et al, 1994] and [Shram et al, 2006]). In contrast, other researchers have reported either avoidance (i.e., an aversion) of the nicotine-paired environment ( [Fudala and Iwamoto, 1987], [Horan et al, 1997] and [Jorenby et al, 1990]) or no place conditioning , , [Clarke and Fibiger, 1987], [Rogers et al, 2004], [Shoaib et al, 1994] and [Shram et al, 2006]). Some potential factors that might explain the inconsistent results include age and strain of the rat, pre-exposure to nicotine, and use of a biased versus unbiased procedure (see LeFoll and Goldberg (2005) for a more detailed review).…”
Section: Introductionmentioning
confidence: 90%
“…However, these studies differ in the dose of nicotine that produces a CPP, with some groups showing nicotine CPPs at doses where others demonstrate no effect. In addition, other reports have shown that nicotine produces only a place aversion (Jorenby et al 1990) or has no effect within this design (Belluzzi et al 2004;Clarke and Fibiger 1987;Parker 1992;Rogers et al 2004;Vastola et al 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, these reports only indicated that animals were handled and did not specifically describe these handling conditions. In other cases, the handling occurred only via experimental procedures performed before place conditioning (Rogers et al 2004;Zarrindast et al 2003). Therefore, the effects of earlier handling experience on nicotine CPPs have not been directly explored.…”
Section: Introductionmentioning
confidence: 97%
“…However, in most rodent studies, drugs are administered to the pregnant dam and then discontinued after birth, obviating any crucial postnatal exposure to the offspring. In addition, current models utilizing only postnatal administration of either nicotine or EtOH (Aramakis et al 2000;Broide et al 1996;West 1993) result in significant repetitive stress to the offspring (McCormick et al 2002;Muneoka et al 1997) and/or prolonged separation from the dam and littermates (Rogers et al 2004;West 1993;West et al 1989). Each of these procedural outcomes has been shown to alter catecholaminergic systems in the developing brain (Choong and Shen 2004;Fung 1989;Hall et al 1999;Lichtensteiger et al 1988;Matthews et al 2001;Muneoka et al 1997;Nulman et al 1998;Shen et al 1999;Slotkin 1998;Xu and Shen 2001), and it is the dopaminergic system, specifically, that plays a major role in the acquisition of drug-taking behavior (Di Chiara 2000;Wise 1996).…”
Section: Introductionmentioning
confidence: 95%